Identification of Physiotherapy Problems in Patients with Chronic Obstructive Pulmonary Disease at Respira Hospital Yogyakarta: An Observational Study - Kusumaningtyas, Mei; Handari, Herdianty Kusuma; Prayitno, Prayitno (Indonesian Journal of Medicine, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality worldwide. Common symptoms include dyspnea, chest pain, reduced thoracic expansion, and impaired pulmonary function. This study aimed to identify physiotherapy-related problems among patients with COPD at Respira Hospital Yogyakarta. Subject and Methods: This observational study was conducted from June to August 2025 at the Physiotherapy Outpatient Clinic of Respira Pulmonary Hospital, Yogyakarta. Physiotherapy-related problems were assessed using the modified Medical Research Council (mMRC) Dyspnea Scale, COPD Assessment Test (CAT), thoracic mobility measurements, Visual Analog Scale (VAS), Peak Flow Meter (PFM), and Incentive Spirometer. Results: A total of 102 patients with COPD participated in the study. Most participants were male (60.8%). Grade 2 dyspnea was reported by 50.0% of subjects, while 65.7% had moderate COPD symptoms. Impaired thoracic mobility was observed in 40.2%–47.1% of patients. Chest pain was reported by only one subject. Severe airflow obstruction was found in 60.8% of participants, with a mean peak expiratory flow of 52.08% of the predicted value. Impaired inspiratory capacity was identified in 48.0% of subjects. Conclusion: The main physiotherapy-related problems identified among patients with COPD at Respira Hospital Yogyakarta were dyspnea, COPD symptoms, impaired thoracic mobility, reduced peak expiratory flow, and decreased inspiratory capacity.